Marketing - Pride, William M.
Engaging and motivating students with diverse backgrounds and different interest levels in marketing requires stimulating and effective teaching materials-and Pride/Ferrel continues to be the resource of choice for instructors. Combining contemporary coverage of marketing strategies and concepts with real-world examples, this text and its outstanding suite of supplements supply students with the knowledge and decision-making skills they'll need to succeed in today's competitive business environment. Topical issues including customer relationship management, supply chain management, the latest e-commerce models, and the current re-evaluation of dot-coms are just a few examples the authors use to connect marketing to students' personal lives. The latest edition also features a new design and additional photos, providing a fresh contemporary look and feel to the text